Решить уравнение: (х-4)²(х-3)=0 (х²-4)(х+1)=0 х(х²+4)(х+4)=0 (х-5)(х³+1)=0

lancerevol12p0cjct lancerevol12p0cjct    2   25.07.2019 12:00    1

Ответы
Danila29012006 Danila29012006  03.10.2020 12:33
( x - 4)^2(x- 3) = 0
x - 4 = 0
x = 4
x - 3 = 0
x = 3

(x^2 - 4)(x + 1) = 0
x^2 - 4 = 0
x^2 = 4
x = 2
x = - 2
x+ 1 = 0
x = - 1

x(x^2 + 4)(x + 4) = 0
x = 0
x^2 + 4 = 0
x^2 = - 4 - корней нет
x + 4 = 0
x = - 4

( x - 5)(x^3 + 1) = 0
x - 5 = 0
x = 5
x^3 + 1 = 0
x^3 = - 1
x = - 1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра